The Effect of Substitution of WC by TiC in WC-Co Composite Tool Materials on Microstructure and Mechanical Properties - Jan Dutkiewicz (Science Faculty of Chiang Mai University, 2019)
WC-Co composites with TiC additions of 5-20 wt.% substituting WC were consolidated using Hot Isostatic Pressing (HIP) method at temperature of 1350°C and pressure between 50-150 MPa. The hardness of WC-Co consolidated samples increase from 1050 HV (without TiC consolidated at 50 MPa) up to 1330 HV at 5% TiC and up to 1600 HV with 20% of TiC. The higher hardness of samples with TiC additions can be explained by a higher consolidation pressure of 150 MPa leading to a lower porosity, but also to hardening due to TiC addition. Young modulus values are lower for samples with TiC attaining 420-490 GPa as compared to 570 GPa for conventional WC-Co samples. Samples with a crack formation behavior allowed to determine fracture toughness KIC using crack length from hardness measurements. Results in the range 10, 9-11, 2 [MPam1/2] for the samples containing 0-10 % TiC, indicated only insignificant decrease of this property with TiC content. Addition of TiC causes also 15-30 % lower density of composites in the range 10-12, 5 g/cm3. The major identified phase is the hexagonal WC carbide separated by a narrow layer of Co binder and accompanied by single particles of TiC within Co. The size of WC particles was the same as applied in conventional composites i.e. 2-4 mm, while that of homogeneously distributed TiC were measured as slightly smaller, below 2 mm. Transmission electron microscopy investigations allowed to identify relatively high dislocation density in both cubic TiC and hexagonal WC carbides and different interfaces between WC and TiC carbides and Co binder however no additional phases were detected there. The crystallographic relationship [01-1] TiC || [100] WC was often observed. The appearance of solid solution of TiC with WC near WC/TiC interfaces was discussed.